BENTUK-BENTUK IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN PADA SISWA DI SMP NEGERI 5 ABIANSEMAL - Ni Wayan Arini; Kadek Dwi Sentana Putra; Ni Kadek Puspita Sari (Yayasan Pendidikan Literasi Borneo, 2026)
Environmental care character education is a strategic effort to develop students’ ecological awareness, social responsibility, and environmentally sustainable behavior. This study aims to describe the forms of implementation of environmental care character education among students at SMP Negeri 5 Abiansemal. The study employed a qualitative approach using a single case study design. The research was conducted at SMP Negeri 5 Abiansemal, Badung Regency, Bali. The participants consisted of the principal, teachers, the Adiwiyata Program coordinator, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation studies, and were analyzed using an interactive analysis model involving data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings reveal that the implementation of environmental care character education was carried out through five main forms: (1) habituation of environmental cleanliness through classroom duty schedules and Friday Clean-Up activities; (2) student-based waste management through waste sorting and school waste banks; (3) greening and plant maintenance activities as a medium for internalizing environmental values; (4) collective environmental activities such as river-cleaning programs; and (5) integration of environmental care values into school culture through policies, teacher role modeling, and the Adiwiyata Program. The study indicates that the successful implementation of environmental care character education is supported by the synergy between school culture, a supportive physical environment, active student participation, and the commitment of all school stakeholders. These practices contribute to the development of students’ ecological awareness, responsibility, discipline, and sustainable environmental behavior